PENGARUH BEBAN PAJAK, TUNNELING INCENTIVE DAN DEBT COVENANT TERHADAP TRANSFER PRICING PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DARI SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2015-2018 - Dwikora Harjo (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Transfer pricing is a company policy in determining pricefrom a transaction of intradivision members in a company or interdivision members between two companies either within the country or outside of the country. The objectives of this study were to test influence of tax expenses, tunneling incentive and debt covenant to the transfer pricing. Decision of transfer pricing in this study used dummy indicators. The population in this study was subsector food and beverage company from consumption goods industrial sector registered with the Indonesia Stock Exchange (BEI) in 2015-2018. Sampling technique used purposive sampling and obtained 14 of 25 companies. The data was collected from data of financial statements and annual report. The data analysis method in this study was logistic binerregression analysis with use of SPSS version 22 software. Its determination coefficient value was 64,9% that reflected tax expense, tunneling incentive and debt covenant affected transfer pricing. The results of the study indicated that simultaneously tax expense, tunneling incentive and debt covenant significantly affected to the transfer pricing policy. Whereas, partially the tax and tunneling incentive significantly affected to transfer pricing policy and the debt covenant not affected to the transfer pricing policy.